Eﬀects of concave thoracoplasty on chest circumference and ventilatory function in adolescence with idiopathic scoliosis - Takey Ahmed, Khaled; Mohamed Hamed, Abla; El Hawary, Youssry; El-Nahas, Nesreen G.; Helmy, Akram M.; Hesham Abouelenein, Mohamed (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Adolescent idiopathic scoliosis (AIS) can reduce rib cage volume, which mechanically overloads the respiratory musculature. A current study examines the inﬂuences of concave thoracoplasty on pulmonary function and chest circumference.Methods. This study included thirty AIS patients of both genders, aged 12 to 18 years, who had a concave thoracoplasty with posterior correction. Pulmonary function, Cobb angles, and chest circumferences were measured before surgery, on the ﬁfth day following surgery, and at three months.Results. A paired t-test was used to compare Cobb angles and chest expansion before and after intervention in the AIS-studied group. The statistical analysis stated that there was a signiﬁcant decrease in Cobb angles and chest expansion (p < 0.05) at post-intervention follow-ups compared to pre-intervention measurements with a change percentage of 56.13% and 18.90%, respectively. Bonferroni correction test was employed to evaluate a pairwise intervention for outcome variables that revealed there were insigniﬁcantly increases in vital capacity (VC), forced vital capacity (FVC), and maximal voluntary breathing (MVV) after the intervention compared to before intervention (p > 0.05). In contrast, the pairwise comparison test between pre-inter-vention versus follow-up revealed time eﬀect had signiﬁcantly increased VC, FVC, and MVV at post-intervention compared to 3 months after the intervention with improvement percentages of 16.51%, 16.11%, and 22.16%, respectively.Conclusions. Patients with AIS who underwent concave thoracoplasty showed greater improvements in Cobb angles and pulmonary function tests 3 months after surgical intervention. Future research activities should emphasize elucidating areas of confusion to improve care in the AIS.
Keywords: adolescent idiopathic scoliosis; concave thoracoplasty; pulmonary function test; chest circumference